Phytochrome and phytohormone interplay in tomato: impacts on fruit physiology and quality traits - Bianchetti, Ricardo Ernesto (2017)
Phytochromes (PHYs) and plant hormones have been emerging as important regulators of fleshy fruit physiology and quality traits; however, the relevance of PHY-hormonal signaling crosstalk in controlling fruit development and metabolism remains elusive. This Thesis assesses the role of PHYs and their interplay with auxins, cytokinins and ethylene during the regulation of tomato (Solanum lycopersicum) fruit development and ripening, with a focus on the control of the plastid biogenesis, sugar metabolism and carotenoid accumulation. In Chapter I, we present evidence that the deficiency in PHY chromophore phytochromobilin (PΦB) biosynthesis, which leads to a global deficiency in functional PHYs, represses fruit chloroplast biogenesis in immature fruits and inhibits fruit sugar accumulation by transcriptionally downregulating sink- and starch biosynthesis-related enzymes. Genetic and physiological evidence suggested the involvement of both auxins and cytokinins as mediators of the negative impact of PΦB deficiency on fruit sink strength and chloroplast formation. During the ripening phase, PΦB deficiency was shown to delay the rise in climacteric ethylene production, affecting the ripening initiation rather than its progression. PHY-hormonal signaling crosstalk was shown to be active not only in the more externally positioned fruit tissues (i.e., pericarp) but also in the most inner fruit regions (i.e., columella). We, therefore, concluded that the global deficiency in functional PHY drastically affects fruit sugar metabolism, chloroplast formation as well as the timing of ripening via an intricate interplay involving phytochromes, auxins, cytokinins and ethylene. In Chapter II, we employed fruit-specific RNAi-mediated silencing of PHY genes to shed light on the specific role played by fruit-localized PHYs and their downstream signaling cascades on tomato fruit physiology and quality traits. Data revealed that fruit-localized SlPHYB2 negatively regulates chlorophyll accumulation in immature fruits whereas SlPHYA positively influences the plastid division machinery. Both SlPHYA and SlPHYB2 were shown to play overlapping, yet distinct, roles in controlling fruit starch metabolism and carotenoid biosynthesis. Our data implicated cytokinin signaling-related proteins as mediators of the SlPHYA-dependent regulation of plastid division machinery, and specific AUXIN RESPONSE FACTORs as intermediates in the PHY-mediated regulation of fruit sugar and carotenoid metabolisms. We concluded that fruit-localized SlPHYA- and SlPHYB2-mediated light perception regulate fruit plastid biogenesis as well as sugar and carotenoid metabolisms via coordinated changes in key components of both auxin and cytokinin signaling cascades. Altogether, this study brings important insights into the combined action of PHYs and hormones in the control of fruit plastid biogenesis and highlights that the interplay between PHY-hormonal signaling cascades influences essential features of tomato fruit quality, such as the sugar and carotenoid accumulation